The Numerical Solution of Fractional Diffusion Equation by Using Local Polynomial Regression - Çağlar, Süleyman Hikmet; Çağlar, Hatice Nazan; Özer, Mehmet (Polish Acad Sciences Inst Physics, Al Lotnikow 32-46, Pl-02-668 Warsaw, Poland, 2014)
In this paper, we apply the local polynomial regression for the solution of the one-dimensional fractional diffusion equation. The Caputo fractional derivative is used for the formulation. A numerical example is given to show the application of the present method. The effect of the fractional order (a) of the equation is illustrated by changing a from 1.01 to 1.99.